151k views
3 votes
Using substitution or elimination

9x+3y=-7
y=-3x+4

User Hacketo
by
4.8k points

2 Answers

5 votes

Answer:

No solution

Explanation:

Plug in y=-3x+4 into 9x+3y=-7

9x+3(-3x+4)=-7 Distribute the 3

9x - 9x + 12 =-7 Combine like terms

12 =-7 This statement isn't true. Therefore this is system of has no solution. The lines do not intersect.

User Bruceg
by
5.7k points
4 votes

Answer:

No solution

Explanation:

If we substitute the y into the equation, we get 9x+3(-3x+4)=-7

If we distribute the 3, we get 9x-9x+12=-7

This then cancels out both 9x's and we are left with 12=-7, making it no solution.

User Bharti
by
4.5k points